Dimensi Kepemimpinan Dan Motivasi Terhadap Kinerja Pegawai Koperasi Karyawan PT. Pindad Persero - Hesti Budiwati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2011)
Leadership plays an important role in an organization in an effort to improve achievement and employee performance and employee at the group level or at the organizational level, because performance is not only highlights the technical side but also highlights the work group and managerial as well as the motivation is the driving force that created the excitement of a person so that they would cooperate, to work effectively and integrated with all its efforts to achieve satisfaction. The results show the existence of mutual relationships and significant influence among some other variable data data also showed that the variables affecting leadership, and motivation to employee performance that stated at the percentage of 90.0%, while the remaining 10.0% described or influenced by other factors.